Two Disease-Causing SNAP-25B Mutations Selectively Impair SNARE C-terminal Assembly. Issue 4 (16th February 2018) - Rebane, Aleksander A.; Wang, Bigeng; Ma, Lu; Qu, Hong; Coleman, Jeff; Krishnakumar, Shyam; Rothman, James E.; Zhang, Yongli
Abstract: Synaptic exocytosis relies on assembly of three soluble N -ethylmaleimide-sensitive factor attachment receptor (SNARE) proteins into a parallel four-helix bundle to drive membrane fusion. SNARE assembly occurs by stepwise zippering of the vesicle-associated SNARE (v-SNARE) onto a binary SNARE complex on the target plasma membrane (t-SNARE). Zippering begins with slow N-terminal association followed by rapid C-terminal zippering, which serves as a power stroke to drive membrane fusion. SNARE mutations have been associated with numerous diseases, especially neurological disorders. It remains unclear how these mutations affect SNARE zippering, partly due to difficulties to quantify the energetics and kinetics of SNARE assembly. Here, we used single-molecule optical tweezers to measure the assembly energy and kinetics of SNARE complexes containing single mutations I67T/N in neuronal SNARE synaptosomal-associated protein of 25 kDa (SNAP-25B), which disrupt neurotransmitter release and have been implicated in neurological disorders. We found that both mutations significantly reduced the energy of C-terminal zippering by ~ 10 k B T, but did not affect N-terminal assembly. In addition, we observed that both mutations lead to unfolding of the C-terminal region in the t-SNARE complex. Our findings suggest that both SNAP-25B mutations impair synaptic exocytosis by destabilizing SNARE assembly, rather than stabilizing SNARE assembly as previously proposed. Therefore, our measurements provide insights into the molecular mechanism of the disease caused by SNARE mutations. Graphical Abstract: Highlights: The mechanism by which two SNAP-25B mutations cause disease is unclear. The mutations greatly weaken SNARE C-terminal zippering. The mutations do not affect SNARE N-terminal assembly. The mutations impair t-SNARE folding. The mutations impair SNARE assembly and thus lead to impaired neurotransmission.